Efficient and Durable 3D Self‐Supported Nitrogen‐Doped Carbon‐Coupled Nickel/Cobalt Phosphide Electrodes: Stoichiometric Ratio Regulated Phase‐ and Morphology‐Dependent Overall Water Splitting Performance - Cao, Bo; Cheng, Yan; Hu, Minghao; Jing, Peng; Ma, Zhixue; Liu, Baocang; Gao, Rui; Zhang, Jun (Advanced functional materials, 2019)
The construction of a novel 3D self‐supported integrated NixCo2−xP@NC (0 < x < 2) nanowall array (NA) on Ni foam (NF) electrode constituting highly dispersed NixCo2−xP nanoparticles, nanorods, nanocapsules, and nanodendrites embedded in N‐doped carbon (NC) NA grown on NF is reported. Benefiting from the collective effects of special morphological and structural design and electronic structure engineering, the NixCo2−xP@NC NA/NF electrodes exhibit superior electrocatalytic performance for water splitting with an excellent stability in a wide pH range. The optimal NiCoP@NC NA/NF electrode exhibits the best hydrogen evolution reaction (HER) activity in acidic solution so far, attaining a current density of 10 mA cm−2 at an overpotential of 34 mV. Moreover, the electrode manifests remarkable performances toward both HER and oxygen evolution reaction in alkaline medium with only small overpotentials of 37 mV at 10 mA cm−2 and 305 mV at 50 mA cm−2, respectively. Most importantly, when coupling with the NiCoP@NC NA/NF electrode for overall water splitting, an alkali electrolyzer delivers a current density of 20 mA cm−2 at a very low cell voltage of ≈1.56 V. In addition, the NiCoP@NC NA/NF electrode has outstanding long‐term durability at j = 10 mA cm−2 with a negligible degradation in current density over 22 h in both acidic and alkaline media. Highly dispersed NiCoP nanoparticles embedded in nitrogen‐doped carbon shell (NC) nanowall arrays grown on Ni foam are fabricated as a 3D self‐supported integrated electrode. It displays remarkable hydrogen evolution reaction and oxygen evolution reaction bifunctionality as well as overall water splitting performance on account of the strong coupling effect between NiCoP nanoparticles and NC shells.